Coming to Terms (RLE Feminist Theory) : Feminism, Theory, Politics. - Weed, Elizabeth (Routledge library editions. Feminist theory., 2012)
For over a decade, feminist studies have occupied an extraordinary position in the United States. On the one hand, they have contributed to the development of a strong 'identity' politics; on the other, they have been part of the post-structuralist critique of the unified subject - its experience, truth and presence - and of the massive challenge to Western metaphysics and humanism. Along with race and ethnic studies, feminist enquiry has moved beyond the fiction of a unitary feminism to address the differences within the study of difference. The essays in this volume all address femi.